Automatically Partitioning 3D Objects for Larger Printing Volumes - Thielo, Marcelo; Jarczewski, Rafael; Tamiosso, Gustavo; Dullius, Douglas; Flores, Eliezer (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2023: Anais da XXXVI Conference on Graphics, Patterns and Images, 2023)
The additive manufacturing(AM) market, popularly known as 3D printing, has proven to be useful and revolutionary for various industry segments. However, 3D printing machines have a physical limitation linked to their printing volume, which leads to the partitioning of objects for larger printing. This work aims to present a 3D object partitioning approach taking into account the desired printing dimensions and the resulting parts' curvatures. We also developed a prototype that receives a 3D object as input and returns a set of cubic partitions, each one seeking maximum advantage of the print volume when possible, through minimization of a cost function. Our solution has an object reader, a visualization interface and the functionality to export the set of objects generated. We also provide a cost function to evaluate characteristics defining the quality of a partitioning, with tests performed manually and employing a genetic algorithm for optimization. As a future work, we intend to evaluate the proposed cost function with more complex objects as well as improving the optimization algorithm so to automatically obtain a set of parameters for partitioning 3D objects for high quality 3D printing.